Schisandrin B decreases the sensitivity of mitochondria to calcium ion-induced permeability transition and protects against ischemia-reperfusion injury in rat hearts - Chiu Po-yee; Leung Hoi-yan; Siu Ada HL; Poon Michel KT; Ko Kam-ming (Acta Pharmacologica Sinica, 2016)
Aim: In order to elucidate the molecular mechanism underlying the cardioprotection afforded by schisandrin B (Sch B), the effect of Sch B treatment on the sensitivity of mitochondria to Ca2+-stimulated permeability transition (PT) was investigated in rat hearts under normal and ischemia-reperfusion (I-R) conditions. Results: Myocardial I-R injury caused an increase in the sensitivity of mitochondria to Ca2+-stimulated PT in vitro. The enhanced sensitivity to mitochondrial PT was associated with increases in mitochondrial Ca2+ content as well as the extent of reactive oxidant species production in vitro and cytochrome c release in vivo. The cardioprotection afforded by Sch B pretreatment against I-R-induced injury was paralleled by the decrease in the sensitivity of myocardial mitochondria to Ca2+-stimulated PT, particularly under I-R conditions. Conclusion: The results suggest that Sch B treatment increases the resistance of myocardial mitochondria to Ca2+-stimulated PT and protects against I-R-induced tissue injury.